ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PT. UNILEVER INDONESIA Tbk. - Efi Herawati; Kafidin Muzakki (Universitas Nahdlatul Ulama Sidoarjo, 2021)
This study aims to assess the level of financial performance of PT. Unilever Indonesia Tbk. period 2014-2018 based onliquidity ratios, solvability ratios, activity ratios, and profitability ratios. The research approach used is qualitative. Thesubjects in this study were PT. Unilever Indonesia Tbk. while the object of this research is PT. Unilever Indonesia Tbk. period 2014-2018. The analysis technique used is to calculate and analyze the financial statements of PT. Unilever Indonesia Tbk. with financial ratio analysis (liquidity ratios, solvability ratios, activity ratios and profitability ratios). The results of this study indicate that PT. Unilever Indonesia Tbk. based on the liquidity ratios in a bad condition because cashand cash equivalents are unable to guarantee its current debt. Solvability ratios in the value of the debt to asset ratio and debt to equity ratio show that the amount of debt that is not proportional to the amount of capital that results in the income generated is used to pay off obligations rather than internal needs. The ratio of activities valued at receivable turnover andinventory turnover of PT. Unilever Indonesai Tbk. in a bad condition this is proven by the decreasing value of the ratio and based on the calculation of the asset turnover of PT. Unilever Indonesia Tbk. in good condition because it can maximize the assets owned. Profitability ratios assessed by net profit margins in conditions are not good, this is evidenced by the decline in the value of the ratio from 2014 to 2016 and declined significantly in 2018 but based on returns on assets and return on equity of PT. Unilever Indonesia Tbk. in good condition.